National Journal Articles Writing for Teachers of Early Childhood Education (PAUD) In Tegal City - Syamsul Anwar; M Arif Budiman S; R Samidi; Fitriyanto Fitriyanto (Universitas Pancasakti Tegal, 2021)
Writing is one indicator for a teacher to be professional. Unfortunately, not all teachers are involved in this activity. It is better if PAUD teachers make writing activities necessary and obligated to produce their desires and thoughts. PAUD teachers are not only required to like to write articles but also actively produce written works that contain creative ideas or thoughts. The teacher will get several benefits from writing, including it can relieve stress, as a memory storage tool, a means of solving problems, and train teachers to think in an orderly and orderly manner. Therefore, it is essential and urgent to conduct training in writing scientific articles for journals for PAUD teachers. Through this activity, it hopes that teachers will be motivated to develop scientific works in the form of scientific articles published in scientific journals. In addition, institutions that serve scientific articles from activity participants can publish them in existing journals.